2022
DOI: 10.24018/ejgeo.2022.3.6.356
|View full text |Cite
|
Sign up to set email alerts
|

Validation of SoilGrids 2.0 in an Arid Region of India using In Situ Measurements

Abstract: As one of the Earth’s most important natural resources, soil plays a prominent role in regulating ecosystem services, human food production systems and in facilitating a region’s sustainable development. Of late, due recognition has been given to soil sciences and soil information systems as they act as a core to achieve the targets of land degradation neutrality and help in fostering soil governance. In this regard, the availability of global soil databases paves the way for implementing successful soil infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…The relationships for soil texture found here were similar to those reported in France (Caubet et al., 2019 ), another area with high density of training data. Results in regions with fewer training points are more variable: no relationships were found between SoilGrids texture predictions and field textures in Norway or Croatia (Huang et al., 2022 ; Radočaj et al., 2023 ), whereas results in arid regions in India were similar to what we observed here (Dandabathula et al., 2022 ). This suggests that biases or noise in SoilGrids predictions of soil texture may be related to regional differences in drivers of soil texture variation rather than the density of training data.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The relationships for soil texture found here were similar to those reported in France (Caubet et al., 2019 ), another area with high density of training data. Results in regions with fewer training points are more variable: no relationships were found between SoilGrids texture predictions and field textures in Norway or Croatia (Huang et al., 2022 ; Radočaj et al., 2023 ), whereas results in arid regions in India were similar to what we observed here (Dandabathula et al., 2022 ). This suggests that biases or noise in SoilGrids predictions of soil texture may be related to regional differences in drivers of soil texture variation rather than the density of training data.…”
Section: Discussionsupporting
confidence: 81%
“…Results in regions with fewer training points are more variable: no relationships were found between SoilGrids texture predictions and field textures in Norway or Croatia(Huang et al, 2022;Radočaj et al, 2023), whereas results in arid regions in India were similar to what we observed here(Dandabathula et al, 2022). This suggests…”
supporting
confidence: 77%
See 1 more Smart Citation